FOLIAGE APLLIED GIBBERELIC ACID INFLUENCES GROWTH, NUTRIENT CONTENTS AND QUALITY OF LETTUCES (LACTUCA SATIVA L.) - V. N. Le; Q. T. Nguyen; N. T. Nguyen; T. Janda; G. Szalai; T. D. Nguyen; T. G. Le (Journal of Animal and Plant Sciences, 2021)
Plant growth regulators (PGRs) have been considered as agrochemicals applied widely in agricultural production, wherein, gibberelic acid (GA3) has gained an interest in using to enhance the growth and improve yield for various vegetables. In this work, lettuces were sprayed with GA3 at different concentration of 0, 10, 30, 50 and 100 mg L-1, respectively, at three dates after transplanting (the 7-day, the 14-day, and the 21-day). The impacts of GA3 on the growth, nutrient elements, and the absorption of heavy metals in lettuces were investigated. The accumulation of GA3 by lettuce plants were confirmed by liquid chromatography - tandem mass spectrometer system (LC-ESI-MS/MS). The results demonstrated, that low concentrations of GA3 (10 and 30 mg L-1) increased the plant height, number of leaves and fresh weight of lettuces, whereas the opposite results were reported in high concentration of GA3 treatment (100 mg L-1). In addition, GA3 decreased nutrient contents of Fe and Mn, and heavy metals’ absorption in lettuces. However, the higher concentrations of GA3 treatment use, the more their accumulations were found in lettuce samples. To the best of our knowledge, this is the first investigation of the influences of GA3 on nutrient elements and the absorption of heavy metals in lettuce. This is needed to further investigate the improvement of crop production efficiency with PGRs, and to minimize their harmful impact on human health and the ecological environment.
Keywords: GA3; heavy metals; lettuce; nutrients